2017
DOI: 10.1371/journal.pone.0182492
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome-wide methylation analysis of longissimus dorsi muscles between Japanese black (Wagyu) and Chinese Red Steppes cattle

Abstract: DNA methylation is an important epigenetic mechanism involved in expression of genes in many biological processes including muscle growth and development. Its effects on economically important traits are evinced from reported significant differences in meat quality traits between Japanese black (Wagyu) and Chinese Red Steppes cattle, thus presenting a unique model for analyzing the effects of DNA methylation on these traits. In the present study, we performed whole genome DNA methylation analysis in the two br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
(48 reference statements)
2
21
0
Order By: Relevance
“…A previous study also reported that S. aureus-positive cattle had significantly more methylation sites on BTA 11 than S. aureusnegative controls (Song et al, 2016), implying a potential regulatory role of DNA methylation in response to S. aureus mastitis. We observed the intergenic and intron regions had more methylation sites (adjusted P < 0.05) compared with other functional gene elements, which is in agreement with previous studies in other cattle breeds (Song et al, 2016;Fang et al, 2017;Chen et al, 2019,a). Similar to results obtained with other mammalian species (Gim et al, 2015;Song et al, 2016;Zhang Y. et al, 2017), the methylation level was DMEGs, the C m CGG differently methylated genes with significantly different gene expression level in the same animal model; BP, biological process; CC, cellular component.…”
Section: Global Dna Methylation Pattern Of Mammary Gland Tissues Revesupporting
confidence: 92%
“…A previous study also reported that S. aureus-positive cattle had significantly more methylation sites on BTA 11 than S. aureusnegative controls (Song et al, 2016), implying a potential regulatory role of DNA methylation in response to S. aureus mastitis. We observed the intergenic and intron regions had more methylation sites (adjusted P < 0.05) compared with other functional gene elements, which is in agreement with previous studies in other cattle breeds (Song et al, 2016;Fang et al, 2017;Chen et al, 2019,a). Similar to results obtained with other mammalian species (Gim et al, 2015;Song et al, 2016;Zhang Y. et al, 2017), the methylation level was DMEGs, the C m CGG differently methylated genes with significantly different gene expression level in the same animal model; BP, biological process; CC, cellular component.…”
Section: Global Dna Methylation Pattern Of Mammary Gland Tissues Revesupporting
confidence: 92%
“…The PI3K-Akt signaling pathway is critical for skeletal muscle protein synthesis and degradation [18]. The calcium signaling pathway is the key pathway exerting allosteric regulation on many proteins, including through ion channel activation or by acting as a secondary messenger, which could directly affect skeletal muscle metabolism [7]. As muscle is a major metabolic tissue, it was not unexpected that metabolic pathways, including carbon metabolism, insulin secretion, and insulin signaling, were enriched in our study.…”
Section: Discussionmentioning
confidence: 65%
“…The muscle of genome-wide methylation patterns were similar between fetus and adult in functional genomic regions. However, there were differences among the three mC contexts which might be related to differences in the sequences of the different genetic elements [7]. After filtering the WGBS-seq raw data, we obtained 230 million clean reads per sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently an increasing number of studies have demonstrated that nutritional or environmental changes contribute to changes in inheritable epigenetic modifications, such as DNA methylation (Lan et al, 2013a;Chavatte-Palmer et al, 2018;Kwan et al, 2018;Yuan et al, 2018). As one of the most important and common types of epigenetic modification, DNA methylation plays a significant role in regulating biological processes such as milk production and organ development (Hwang et al, 2017;Fleming et al, 2018;Jessop et al, 2018). In recent years, gene methylation involved in vital biological functions has been wellstudied in animals (Ibeagha-Awemu and Zhao, 2015).…”
Section: Introductionmentioning
confidence: 99%